Estimation of the wastage rate of MMR and pentavalent vaccines in open and closed vials in three western provinces of Iran. Issue 5 (May 2020) - Zahraei, Seyed Mohsen; Zamani, Golamabbas; Mohammadbeigi, Abolfazl; Asgarian, Azadeh; Afrashteh, Sima; Gharibnavaz, Hassan; Haghgou, Mojtaba; Kone, Souleymane
Abstract: Background: Vaccine wastage is one of quality indicators of immunization program and high vaccine wastage will increase overall costs and impede efforts towards a more efficient and sustainable program. We aimed at estimating of the wastage rates of Measles-Mumps-Rubella (MMR) and pentavalent (diphtheria-tetanus-pertussis-hepatitis B -Haemophilus influenza type b) vaccines in different vaccine vial sizes. Study design: Multicentre descriptive study using existing data. Methods: This study was in three provinces (Hamadan, Kermanshah and Kordestan) of Iran including 131, 135 populations with 2, 548 under-1years children. Twenty-seven health facilities were selected randomly from nine districts in three provinces of western part of Iran. Six-months data including vaccination and vaccine stock records collected from April to September 2017. Finally, number of opened vials and number of target population vaccinated were collected and data were analysed to estimate the wastage rates in both unopened and opened vials of both antigens. Results: The wastage rate for combined MMR 2-dose and 5-dose opened vials for three provinces was 29%(Hamadan 18%, Kermanshah 14% and Kordestan 52%). The wastage rate for combined pentavalent single-dose and 10-dose vials for three provinces was 17% (in Kordestan33%, 11% Kermanshah 11% and Hamedan 3%). The total average of pentavalent single-dose and 10-dose vials wastage rate was 5% and varied 13% for urban and 3% for rural areas. The average of discarded unopened vials wastage rate in all facilities for MMR was 3.9% (3.2% for MMR 2-dose vial and 10.2% for MMR 5-dose vial). This rate was 1.7% for pentavalent total (1.9% for single dose vial and 0.4% for 10 dose vial). Conclusion: The vaccine wastage rates in Iran are in line with other countries and lower than the suggested rate based on WHO policies for multi-dose vials. The wastage rates were different for in provinces, districts and health facilities. The MMR total wastage rate in rural is higher than those in urban areas. However, the pentavalent total wastage rate was higher in urban area. Abstract : Public Health; Wastage rate; Pentavalent; Vaccine; MMR; Iran; Vaccination.